Auxin-Inducible Depletion of the Essentialome Suggests Inhibition of TORC1 by Auxins and Inhibition of Vrg4 by SDZ 90-215, a Natural Antifungal Cyclopeptide. Issue 3 (1st March 2019) - Snyder, Nathan A; Kim, Adam; Kester, Louis; Gale, Andrew N; Studer, Christian; Hoepfner, Dominic; Roggo, Silvio; Helliwell, Stephen B; Cunningham, Kyle W
Abstract: Gene knockout and knockdown strategies have been immensely successful probes of gene function, but small molecule inhibitors (SMIs) of gene products allow much greater time resolution and are particularly useful when the targets are essential for cell replication or survival. SMIs also serve as lead compounds for drug discovery. However, discovery of selective SMIs is costly and inefficient. The action of SMIs can be modeled simply by tagging gene products with an auxin-inducible degron (AID) that triggers rapid ubiquitylation and proteasomal degradation of the tagged protein upon exposure of live cells to auxin. To determine if this approach is broadly effective, we AID-tagged over 750 essential proteins in Saccharomyces cerevisiae and observed growth inhibition by low concentrations of auxin in over 66% of cases. Polytopic transmembrane proteins in the plasma membrane, Golgi complex, and endoplasmic reticulum were efficiently depleted if the AID-tag was exposed to cytoplasmic OsTIR1 ubiquitin ligase. The auxin analog 1-napthylacetic acid (NAA) was as potent as auxin on AID-tags, but surprisingly NAA was more potent than auxin at inhibiting target of rapamycin complex 1 (TORC1) function. Auxin also synergized with known SMIs when acting on the same essential protein, indicating that AID-tagged strains can be useful for SMI screening. Auxin synergy, resistance mutations, and cellular assays together suggest the essential GMP/GDP-mannose exchanger in the Golgi complex (Vrg4 ) as the target of a natural cyclic peptide of unknown function (SDZ 90-215). These findings indicate that AID-tagging can efficiently model the action of SMIs before they are discovered and can facilitate SMI discovery.